All-Silicon Energy-Efficient Optical Diode Using Opto-Mechanical Microring Resonators - Linghuan Xu; Li Liu; Miaomiao Chen; Mengyuan Ye (IEEE Photonics Journal, 2020)
By utilizing two cascaded all-silicon opto-mechanical microring resonators (MRRs), an energy-efficient optical diode with high nonreciprocal transmission ratios (NTRs) is proposed and experimentally realized. The optical diode is composed of an all-pass opto-mechanical MRR and an add-drop opto-mechanical MRR. Due to the largely enhanced interaction between the photons and the suspended structure, the opto-mechanical effect can be dramatically improved. With injecting low optical powers, the optical gradient force can be effectively aroused in the opto-mechanical MRRs, which would arise nano-meter scale waveguide deformations and the significant spectrum red-shifts of the rings. The opto-mechanical effect would cause different red-shifts of the two MRR resonances in the forward and backward transmissions, which contributes to realizing the nonreciprocal transmissions. The experimental results show that with −4.2 dBm power consumption, the optical diode can achieve high NTRs approach 41.8 dB. Due to the dominant advantages of complementary metal oxide semiconductor (COMS) compatibility, high NTRs (41.8 dB), low power consumption (−4.2 dBm) and compact size (0.015 mm2), the device has remarkable applications in on-chip signal processing systems.